Implementasi Algoritma AES-256 Berbasis Web untuk Pengamanan Dokumen Digital di CV. Karya Eksklusif Nusantara - Naqiyah, Ainun; Hayati, Lilis Nur; Faradibah, Amaliah (Universitas Gunadarma, 2025)
In the digital era, corporate document security has become a major challenge due to the increasing risk of data breaches and cyberattacks. CV. Karya Eksklusif Nusantara, a company that provides goods and services, still stores important documents in digital formats such as .pdf, .docx, and .xlsx without a special protection system, making them vulnerable to illegal access or data corruption. This study aims to implement the AES-256 algorithm in CBC mode on a web-based system to encrypt and decrypt digital documents, as well as to test its performance based on different file sizes. This research uses the Waterfall method, which includes stages of data collection through interviews and literature review, system requirement analysis, design using UML, implementation with the Laravel framework, and black-box testing. The result of the study is a web-based application capable of securely encrypting and decrypting digital documents. Performance testing shows that the encryption and decryption operations are very fast, with an average encryption time of 0.2924 seconds and a decryption time of 0.3309 seconds, while functional testing ensures that all functions work according to requirements.